Pengaruh Gaya Kepemimpinan Dan Lingkungan Kerja Terhadap Kinerja Pegawai Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Sleman DIY - Yuliantoharinugroho, Yuliantoharinugroho; Mochamad Rofik; Himawan Agung Nugroho; Evi Ria Anggraeni (LPPM Akademi Manajemen Administrasi Yogyakarta, 2024)
This research aims to determine the influence of leadership style and work environment on employee performance at the Population and Civil Registration Service of Sleman Regency, DIY. The research method used in this research is a quantitative method. The data used is primary data obtained from distributing questionnaires to Sleman Dukcapil employees. Sampling in this study used a non-probability sampling method, a saturated sample with a total of 83 respondents. The analysis in this research uses multiple linear regression analysis. The results of the research show that the leadership style variable (X1) has no partial effect on employee performance (Y) as shown by the t-count value (-0.330) < t-table (1.99006), with a significance level of 0.742 which is greater than 0.05 . The work environment variable (X2) has a partial effect on employee performance (Y), shown by t-count 8.221 > t-table (1.99006), with a significance level of 0.000 less than 0.05.